HRES-1/Rab4-mediated depletion of Drp1 impairs mitochondrial homeostasis and represents a target for treatment in SLE. Issue 10 (29th July 2013) - Caza, Tiffany N; Fernandez, David R; Talaber, Gergely; Oaks, Zachary; Haas, Mark; Madaio, Michael P; Lai, Zhi-wei; Miklossy, Gabriella; Singh, Ram R; Chudakov, Dmitriy M; Malorni, Walter; Middleton, Frank; et al.
Abstract : Objective: Accumulation of mitochondria underlies T-cell dysfunction in systemic lupus erythematosus (SLE). Mitochondrial turnover involves endosomal traffic regulated by HRES-1/Rab4, a small GTPase that is overexpressed in lupus T cells. Therefore, we investigated whether (1) HRES-1/Rab4 impacts mitochondrial homeostasis and (2) Rab geranylgeranyl transferase inhibitor 3-PEHPC blocks mitochondrial accumulation in T cells, autoimmunity and disease development in lupus-prone mice. Methods: Mitochondria were evaluated in peripheral blood lymphocytes (PBL) of 38 SLE patients and 21 healthy controls and mouse models by flow cytometry, microscopy and western blot. MRL/lpr mice were treated with 125 μg/kg 3-PEHPC or 1 mg/kg rapamycin for 10 weeks, from 4 weeks of age. Disease was monitored by antinuclear antibody (ANA) production, proteinuria, and renal histology. Results: Overexpression of HRES-1/Rab4 increased the mitochondrial mass of PBL (1.4-fold; p=0.019) and Jurkat cells (2-fold; p=0.000016) and depleted the mitophagy initiator protein Drp1 both in human (−49%; p=0.01) and mouse lymphocytes (−41%; p=0.03). Drp1 protein levels were profoundly diminished in PBL of SLE patients (−86±3%; p=0.012). T cells of 4-week-old MRL/lpr mice exhibited 4.7-fold over-expression of Rab4A (p=0.0002), the murine homologue of HRES-1/Rab4, and depletion of Drp1 that preceded the accumulation of mitochondria, ANA production and nephritis. 3-PEHPC increased Drp1 (p=0.03) and reduced mitochondrial mass in T cells (p=0.02) and diminished ANA production (p=0.021), proteinuria (p=0.00004), and nephritis scores of lupus-prone mice (p<0.001). Conclusions: These data reveal a pathogenic role for HRES-1/Rab4-mediated Drp1 depletion and identify endocytic control of mitophagy as a treatment target in SLE.